Beyond Academic Math: The Role of Applied STEM Course Taking in High School. Issue 7 (July 2014) - Gottfried, Michael A.; Bozick, Robert; Srinivasan, Sinduja V.
Background/Context: Educational policymakers and researchers are concerned about the declining quantity and quality of U.S. students in line to pursue careers in science, technology, engineering, and mathematics (STEM) fields. As one policy response, a number of federal initiatives have been enacted to enhance STEM curriculum in schools. Part of this push has been to offer applied STEM courses in the K–12 curriculum to reinforce academic STEM material as well as motivate students to remain in these fields. Prior to this current study, no national-level research has evaluated the effectiveness of these courses. Purpose: (a) What applied STEM courses are most commonly taken by high school students? (b) To what extent are high school students taking both academic math courses and applied STEM courses? (c) Do applied STEM courses in high school improve achievement in math? Participants: To address the three research questions listed above, this study relies on a comprehensive longitudinal dataset: the Education Longitudinal Survey (ELS:2002). The present study is based on a sample of approximately 11, 112 students who participated in the base-year (10th grade, 2002) and first follow-up (12th grade 2004) interviews, who completed math assessments in both years, and for whom valid transcript information was collected. Research Design: This study begins with a descriptive analysis to evaluate which students have taken applied STEM courses and at which ability level. From this, a common set of applied STEM courses is determined across this nationally representative dataset. Next, this study relies on a linear regression model of math achievement where the dependent variable is a standardized math score. Independent covariates include measures as to whether or not a student had taken applied STEM courses, academic math courses taken by the student, and a range of controls. Findings: Students who take an applied STEM course had higher math scores than their peers who did not take an applied STEM course, all else equal. These courses may be particularly beneficial for those students who are less oriented toward advanced math. Conclusions/Recommendations: Applied STEM courses can be used to support learning in math instructed elsewhere in the curriculum, particularly for those students at the lower end of the math pipeline. In providing hands-on learning, often with technology and with direct application to concrete occupationally specific problems, applied STEM courses may serve as a critical means to support an understanding of concepts taught in lower level math pipeline courses.